Civic Education and Political Participation in The Digital Era: Indicators and Strategies From a Systematic Review - Sekarsari, Peni; Aprilianata, Aprilianata; Murdiono, Mukhamad; Suyato, Suyato (Universitas Negeri Malang, 2025)
This study aims to identify forms of civic education implementation, analyze indicators of political participation on social media, and formulate an ideal civic education model to increase political articipation on social media. The method used is a systematic literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses approach. The results of the study of 56 articles show that civic education for civil society is carried out through expressive participation on social media, learning in schools, political activities, civil organizations and communities, social discussions and interactions, and education in the family environment. There are six indicators of political participation on social media, namely participation in political discussions on social media, online election campaigns, sharing political content, signing online petitions, using hashtags, and liking and commenting on political content. Political participation on social media can increase if it is supported by the implementation of civic education that prioritizes four aspects, namely digital literacy, inclusiveness, ethical discourse, and holistic integration.